Policies and Programmes on ECCE in India: An Evaluation - Choudhary, Sujit Kumar (JOURNAL OF INDIAN EDUCATION, 2012)
The World Education Forum in Dakar, Senegal approved a comprehensive vision of Education For All (EFA) to be achieved by 2015 based on the six goals. The six goals related to the areas of Early Childhood Care and Education (ECCE), universalising primary education, gender, youth and adolescents, adult education and quality of education. In the very first goal, EFA emphasises on expanding and improving comprehensive ECCE, especially the most vulnerable and disadvantaged children. The main focus is on ‘reaching the unreached’ for ensuring complete coverage of education. Indian Constitution directs the state to provide free and compulsory education for all children up to the age of 14 years. This goal has been pursued by India for nearly six decades through different programmes. The last two decades have witnessed significant improvements in children’s participation in schooling. The recent effort to raise resources for the sector through imposition of an education cess is major effort in that direction. The present paper focuses and analyses various policies and programmes on ECCE in India and also tries to evaluate these.